1999
DOI: 10.1001/jama.282.22.2131
|View full text |Cite
|
Sign up to set email alerts
|

Elevated C-Reactive Protein Levels in Overweight and Obese Adults

Abstract: Higher BMI is associated with higher CRP concentrations, even among young adults aged 17 to 39 years. These findings suggest a state of low-grade systemic inflammation in overweight and obese persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

126
1,263
17
41

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,119 publications
(1,488 citation statements)
references
References 41 publications
126
1,263
17
41
Order By: Relevance
“…Several studies have shown that CRP is elevated in human obesity [36,37] and that it is correlated with indicators of adiposity [37][38][39][40][41]. These discrepancies may be explained taking into account several methodological aspects of the present study.…”
Section: Discussionmentioning
confidence: 76%
“…Several studies have shown that CRP is elevated in human obesity [36,37] and that it is correlated with indicators of adiposity [37][38][39][40][41]. These discrepancies may be explained taking into account several methodological aspects of the present study.…”
Section: Discussionmentioning
confidence: 76%
“…This is in agreement with the study by Hak et al 31 who also reported an independent association between WC and CRP levels. Visser et al 32 showed positive relationships between obesity (BMIX30.0 kg m À2 ), elevated WHR and CRP.…”
Section: Discussionmentioning
confidence: 98%
“…To address this question, we used a benchmarking approach (Sechrest et al, 1996) These results have implications for neurodegenerative models of inflammation. Higher body mass has been consistently linked with increased inflammation (Visser et al, 1999 andWisse, 2004) as well as lower cognitive functioning (Benito-León et al, 2013, Cournot et al, 2006and Memel et al, 2016, and higher levels of inflammation predicts cognitive decline (Perry et al, 2007, Tegeler et al, 2016, Teunissen et al, 2003and Yaffe et al, 2003, but no previous studies have tested the associations body mass, inflammation, and cognitive decline in a single, integrated model. Once a robust link between a biometric risk factor, such as body mass, and an outcome of clinical interest is established, it essential to test the more proximal potential biological mechanisms that might help explain this association using mediation models that integrate the relevant biological intermediary into the pathways from risk factor to outcome (Miller et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…There are several pathways through which body mass might influence changes in cognitive functioning over time. For example, greater adipose tissue and body mass, for example, increases the production of proinflammatory cytokines tied to metabolic syndrome (Wisse, 2004) and greater body mass predicts greater leptin and insulin resistance, insulin dysregulation, and inflammation, all of which are associated with cognitive decline (Consondine et al, 1996;Al Hazzouri, Stone, Haan, & Yaffe, 2013;Greenwood & Winocur, 2005;Visser et al, 1999;Wisse, 2004). One potential biologically-mediated pathway that could explain the association between higher body mass and cognitive decline is inflammation.…”
Section: Body Mass Inflammation and Cognitionmentioning
confidence: 99%